EFFECTS OF STORAGE TEMPERATURE ON THE QUALITY AND QUANTITY OF DNA EXTRACTED FROM MAIZE LEAVES - Kostadinović, Marija; Ristić, Danijela; Lučev, Milica; Ignjatović Micić, Dragana; Vančetović, Jelena (Journal of Agricultural Sciences (Belgrade), 2024)
This study was carried out to evaluate the effect of temperature during storage of maize leaves and extracted DNA on its quality and quantity in order to be efficiently amplified using PCR. Leaves were collected from the four-weeks-old plants and divided into three groups of 20 samples. The first group was processed immediately, while the other two were stored for 30 days at -20°C or -80°C. The DNA extracted from fresh leaves was divided into three portions with the first being amplified immediately and the other two stored for 30 days at -20°C or -80°C. The DNA quality and quantity were examined using biospectrometer, after which samples were diluted for the PCR assay. The quality of all DNA samples were at an acceptable level with their average OD260/280 ratio in the range from 1.85 to 1.87. Concentration of the DNA extracted immediately from fresh leaf tissue was not statistically different from the stored samples. Both quality and quantity of DNA in all samples were sufficient for successful PCR amplification with two opaque2-specific molecular markers. The phi057 amplified 170bp fragment in QPM and 160bp in non-QPM, while umc1066 amplified 150bp fragment in QPM and 160-170bp in non-QPM. Our results indicated that appropriate storage conditions will not affect DNA quality and quantity. This could be useful in marker assisted selection of target gene, when a large number of samples must be processed prior to pollination, allowing breeders to discard plants without allels of interest and reduce the size of breeding population.